Transformation of the scientific area in the context of contemporary challenges - Inna Boychuk, Piotr Zięba, Paulina Kolisnichenko, Yevhen Vorobets, Taisiia Martynova, Andrii Tatarchenko (Publishing House “Baltija Publishing”, Riga, Latvia, 2025)
This scientific monograph presents research on theoretical and practical areas of science in the context of contemporary challenges. The publication encompasses a wide range of subjects within the natural and agricultural sciences, legal and economic sciences, as well as philological and pedagogical sciences. The publication is intended for a wide range of readers, including scientists, educators, postgraduate students, and students.
Transformation of the scientific area in the context of contemporary challenges : Scientific monograph. Riga, Latvia : Baltija Publishing, 2025. 692 p.
Keywords: Transformation; scientific area; contemporary challenges; advertising; PR-system; digital technologies; artificial intelligence; internet; marketing models